2005
DOI: 10.1086/431492
|View full text |Cite
|
Sign up to set email alerts
|

Estimates of Rotavirus Disease Burden in Hong Kong: Hospital‐Based Surveillance

Abstract: Our study combined passive surveillance data from all Hong Kong HA hospitals with active surveillance data from 4 sentinel hospitals. The estimates of rotavirus disease burden obtained will help emphasize the effect of this important disease and create awareness of the potential for rotavirus vaccines. The surveillance model developed could also be a powerful tool for monitoring the effect of a vaccine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
48
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 18 publications
3
48
0
Order By: Relevance
“…The results are generally consistent with previously published data on rotavirus [Nelson et al, 2004[Nelson et al, , 2005a and norovirus [Ho et al, 2006] in Hong Kong. Our results suggest that the proportion of acute gastroenteritis cases caused by norovirus has risen compared to 15-20 years ago (1.9%) [Chan et al, 1994].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The results are generally consistent with previously published data on rotavirus [Nelson et al, 2004[Nelson et al, , 2005a and norovirus [Ho et al, 2006] in Hong Kong. Our results suggest that the proportion of acute gastroenteritis cases caused by norovirus has risen compared to 15-20 years ago (1.9%) [Chan et al, 1994].…”
Section: Discussionsupporting
confidence: 92%
“…This may be the result of a particular outbreak, but is also consistent with previous data also reported a winter predominance of rotavirus in Hong Kong, China and worldwide [Chan et al, 1994;Nelson et al, 2004;Orenstein et al, 2007]. It has been reported that norovirus peaks between October and March in Hong Kong [Nelson et al, 2005a;Ho et al, 2006] and elsewhere . Our results however, showed that the number of norovirus detected remained fairly stable throughout the 8 months.…”
Section: Discussionsupporting
confidence: 90%
“…11 [12][13][14] A rotavirus season was defined as a 12-month period starting from September of a calendar year until the end of August in the following year. 13,15 The occurrence of rotavirus infection was correlated with different meteorological variables recorded during the study period (http://www.weather.gov.hk/wxinfo/pastwx/past.htm).…”
Section: Collection Of Stool Specimens and Seasonalitymentioning
confidence: 99%
“…The World Health Organization (WHO) and UNICEF estimate that almost 2.5 billion episodes of diarrhea occur annually in children <5 year of age in developing countries, with more than 80% of the episodes occurring in Africa and South Asia, 46% and 38%, respectively [1]. In India diarrhea is the third leading killer of children, responsible for 13% of all deaths in children below 5 years of age and kills an estimated 300,000 children in India each year [2].…”
Section: Introductionmentioning
confidence: 99%